Analisis Burn Up pada Reaktor Cepat Berpendingin Gas Menggunakan Bahan Bakar Uranium Alam - Feriska Handayani Irka; Zaki Su’ud (Universitas Andalas, 2015)
Burn up analysis of gas cooled fast reactor (GCFR) with natural uranium fuel has been done. Burn up modification used in order to make reactor can be operated with natural uranium without enrichment. The reactor core subdivided into 10 regions with the same volume in radial directions. Optimization evaluated by burning natural uranium for 100 years and put each of its burn up result per year in reactor with certain configuration. After 10 years burn up period, fuel from first region was shuffling radially to second region and so on fuel from 9th shuffling to 10th and then fuel from 10th was carried out from reactor core and fresh uranium input to the first region. Calculation has been done by using SRAC system code with JENDL-32 as library, with cylindrical two dimensional R-Z core models. Shuffling method was used in order to make reactor can be operated using natural uranium. . This natural uranium initially being burned by guessed power level of burn up. The height and diameter core are 350 cm and 240 cm respectively. The volume fraction for this design is 65% fuel, 10% cladding and 25% coolant; with output power 700 MWTh. The result show that reactor demonstrated excellent performance with effective multiplication factor 1,055